Predictors and Moderators of Spontaneous Pretend Play in Children with and without Autism Spectrum Disorder - Kang, Erin; Klein, Eliana F.; Lillard, Angeline S.; Lerner, Matthew D. (Frontiers in Psychology, 2016)
Although pretend play has long been linked to children’s normative cognitive development, inconsistent findings call for greater rigor in examining this relation (Lillard et al., 2013). Spontaneous pretend play is often impacted in atypical development, notably in autism spectrum disorder (ASD). Since ASD traits exist along a continuum in the general population, investigating how pretend play varies across the range of ASD symptoms by indexing variations in ASD traits in both typically-developing and ASD populations may provide insight into how ASD symptoms may influence the relation between pretend play and associated processes in cognitive development. This study used rigorous observational methods to assess spontaneous pretend play. Specifically, 5-minute free-play sessions with two discrete toy sets were double-coded by blinded coders (coder assignment counterbalanced). Key facets of pretense development (attribution of pretend properties, object substitution, imaginary objects) were examined. These facets of pretend play production were then analyzed in relation to ASD symptoms, as well as plausible, long-theorized correlates (Theory of Mind [ToM], verbal ability, familiarity, and interest in specific toys). Forty children (Mage = 6;5, SDage = 1.45; 29 male), six of whom met the threshold for ASD diagnosis via parent-reported ASD symptoms, participated in play sessions and completed measures of verbal IQ and ToM. Besides the measure of child ASD symptoms, parents completed a survey of their child’s interest in and familiarity with the play session toys. Overall, greater ToM predicted more attribution of pretend properties, and more interest in the toys presented predicted more object substitution. In terms of overall pretend play production, two results were counterintuitive. First, among children with more ASD symptoms, verbal ability marginally negatively predicted pretend play production. Second, among children with fewer ASD symptoms, ToM negatively predicted pretend play production. Further probing revealed that the negative effect of ASD symptoms on pretend play was simultaneously moderated by both variables: low ToM and high verbal ability both related to less pretend play production among children with more ASD symptoms. Implications for assessment and subsequent treatment for pretend ability among children with varying degrees of ASD symptoms, as well as for future research, are discussed.